2010
DOI: 10.1039/c0nr00541j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into seeded growth processes of gold nanoparticles

Abstract: A facile approach for the synthesis of monodisperse gold nanoparticles with radii in the range of 7 to 20 nm is presented. Starting from monodisperse seeds with radii of 7 nm, produced in the first step, the addition of a defined amount of additional precursor material permits distinct size regulation and the realization of predicted nanoparticle sizes. These information were derived from ex- and in situ investigations by comprehensive small angle X-ray scattering (SAXS), X-ray absorption near edge structure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 33 publications
6
71
0
Order By: Relevance
“…The few formed seed particles are polydisperse 26,53 but grow into monodisperse AuNP due to a continuous monomer supply during growth steps 3 and 4 which could be described by a size focusing effect. 54 The seed-mediated growth mechanism is actually a fortunate coincidence created by a favorable interplay of different chemical and physicochemical processes as shown in section #3 and illustrated in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 termination of seed particle formation just at an appropriate time frame so that only "very few" seed particles (still in the scale of billions) can be formed.…”
Section: Question #5: Why Does the Citrate Reduction Of Silver Nitratmentioning
confidence: 99%
“…The few formed seed particles are polydisperse 26,53 but grow into monodisperse AuNP due to a continuous monomer supply during growth steps 3 and 4 which could be described by a size focusing effect. 54 The seed-mediated growth mechanism is actually a fortunate coincidence created by a favorable interplay of different chemical and physicochemical processes as shown in section #3 and illustrated in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 termination of seed particle formation just at an appropriate time frame so that only "very few" seed particles (still in the scale of billions) can be formed.…”
Section: Question #5: Why Does the Citrate Reduction Of Silver Nitratmentioning
confidence: 99%
“…[59] The preparation route consists of reduction of the gold precursor HAuCl 4 by dissolved trisodium citrate at 75 • C from aqueous solutions containing 0.25 and 2.5 mmol/l of gold precursor and citrate, respectively. Adding further reactant solution to freshly synthesized gold seeds allows for a precise control of the sizes and polydispersity of the formed nanoparticles (for details see Emmerling et al [34] ). Prior to each experiment, 35 ml aqueous (Millipore) solution of gold precursor (7 mg HAuCl 4 ·3H 2 O, Aldrich) and 35 ml aqueous solution of trisodium citrate (51.45 mg Na 3 C 6 H 5 O 7 ·2H 2 O, Aldrich) were prepared and pre-heated to the reaction temperature (75 • C).…”
Section: Experimental Synthesis and Uv-vis Extinction Characterizatiomentioning
confidence: 99%
“…The shapes, sizes and polydispersity of the gold nanoparticles are determined by small angle X-ray scattering (SAXS). In the synthesis used to generate the nanospheres, sodium citrate serves as both the reducing and capping agent, so that the surface properties are the same for particles of different sizes [34] in order to avoid variation in the chemical SERS enhancement with particle size. We chose as the analyte molecule CV, which is a triarylmethane dye that has been well characterized by SERS, [35 -38] and obtained data under conditions where no aggregation took place.…”
Section: Introductionmentioning
confidence: 99%
“…Biocompatibility, ease of surface-functionalization and scalability to large volumes has made the Turkevich method not only popular amongst researchers but also the method of choice for producing NIST reference standards for biological applications (NIST Reference Materials 8011, 8012 and 8013). Over the last six decades, the Turkevich method has been characterized using several experimental techniques [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. These studies have revealed the key roles of three process parameters: reaction mixture pH, reactant concentration and ionic strength.…”
Section: Introductionmentioning
confidence: 99%